2022
DOI: 10.1177/27539687221124046
|View full text |Cite
|
Sign up to set email alerts
|

The vulnerability of tropical peatlands to oil and gas exploration and extraction

Abstract: Tropical peatlands store globally significant quantities of carbon and are ecologically and culturally important, but little is known about their vulnerability to oil and gas exploration and extraction. Here, we analyse the exposure of tropical peatlands to the activities of the petroleum industry and review what is known about the sensitivity of peatlands to these activities. We find that 8.3% (107,000 km2) of the total area of tropical peatlands overlaps with a 30-km buffer area around oil and gas infrastruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 165 publications
0
2
0
Order By: Relevance
“…This decision also challenges President Tshisekedi, who declared during COP26 that "with its forests, water and mineral resources, the Democratic Republic of Congo is a genuine 'Solution Country' to the climate crisis" (Mukpo 2022). Greenpeace's office in the DRC (2022) has called the government's attention to the potential impacts of this decision, and raised inconsistencies with the decision to auction these oil blocks that overlap not only with peatlands, as shown by Lawson et al (2022), but also with several protected areas in the country:…”
Section: Mining Concessions Oil and Hydrocarbonmentioning
confidence: 99%
See 1 more Smart Citation
“…This decision also challenges President Tshisekedi, who declared during COP26 that "with its forests, water and mineral resources, the Democratic Republic of Congo is a genuine 'Solution Country' to the climate crisis" (Mukpo 2022). Greenpeace's office in the DRC (2022) has called the government's attention to the potential impacts of this decision, and raised inconsistencies with the decision to auction these oil blocks that overlap not only with peatlands, as shown by Lawson et al (2022), but also with several protected areas in the country:…”
Section: Mining Concessions Oil and Hydrocarbonmentioning
confidence: 99%
“…Based on the experience of Indonesia, Dargie et al (2019) hypothesize that high commodity prices, improved access to markets via roads and rivers, and drought due to higher temperatures, could collectively lead to peatland degradation. If the DRC government grants the oil concessions that were validated during the April 2022 Ministerial Council, as well as pending forest and mining concessions for the Cuvette Centrale, such activities could lead to easier access to peatlands, and may increase anthropogenic activities, leading to increasing degradation in the area (Lawson et al 2022). Attention also needs to be paid to combined degradation; examining factors individually can mislead policymakers, as such factors are not always happening at high magnitude.…”
Section: Wetland Biodiversity Lossmentioning
confidence: 99%
“…Oil and gas activities also directly result in deforestation, hydrological damage, and landscape degradation through the development of new infrastructure. A recent assessment by Lawson et al (2022) estimates 8.3% of all tropical peatlands have a potential overlap with a 30 km buffer zone around oil and gas infrastructure, including in Indonesia, the Niger Delta, and he Putumayo-Oriente-Marañón Basin. Oil spills frequently occur around pipelines and shipping routes and can have multiple adverse impacts on tropical peatland ecology, for example through direct toxicity for flora and fauna (Lawson et al, 2022).…”
Section: Land Use Changementioning
confidence: 99%
“…A map of M. flexuosa stands under different levels of degradation is also available, at the local scale and for a single date (Hergoualc'h et al, 2017). Based on national data, Bourgeau-Chavez et al (2021) and Hastie et al (2022) found low deforestation rates within peatlands, due mainly to conversion to agriculture and pasture, however mining, oil drilling activities and new road construction were also identified as potential drivers of deforestation and degradation in the region (Householder et al, 2012;Roucoux et al, 2017;Lawson et al, 2022). Hastie et al (2022) detected increasing deforested areas on peatlands from 2000 to 2016 which generated peat emissions of 4.4 TgC or about 3% of biomass emissions from gross deforestation in the lowland Peruvian Amazon.…”
Section: Introductionmentioning
confidence: 99%